Screening of Tanzanian sweet potato germplasm for yield and related traits and resistance to sweet potato virus disease. (2nd January 2016) - Ngailo, Stephan; Shimelis, Hussein; Sibiya, Julia; Mtunda, Kiddo
Abstract : Sweet potato ( Ipomoea batatas [L.] Lam) is a versatile crop globally serving as food, feed and raw material for industries. Designed selection for higher yields and related traits is crucial to identify complementary sweet potato clones for breeding. The objective of this study was to determine phenotypic variation among diverse sweet potato collections with regard to yield, dry matter content (DMC) and sweet potato virus disease (SPVD) resistance and to identify suitable clones for breeding. A total of 144 sweet potato genotypes were evaluated at 2 sites in Tanzania using a 12 × 12 simple lattice design. Data collected included 10 quantitative and 17 qualitative agro-morphological traits and virus reaction. Results indicated differences among genotypes for most traits studied. The mean DMC was 36% with clones Zapallo and Ukerewe exhibiting the lowest and highest values of 29% and 45%, respectively. The mean storage root yield of clones was 5.1 t/ha with genotype Jewel expressing the highest yield of 11.3 t/ha. Genotypes Resisto and Mataya were early flowering at 40 and 50 days, respectively, while Ex-Mwanza and Kandoro did not flower at all. Fifty-eight per cent of the genotypes showed resistant reaction to SPVD, while 31% and 11% were moderately susceptible and susceptible to the disease, respectively. A positive correlation was observed for the number of roots and fresh root yield. Seven clones including Simama, Ukerewe, Mataya, Resisto, 03–03, Ex-Msimbi-1 and Gairo were selected for high storage root yield and related traits or SPVD resistance. The selected genotypes are recommended as potential parents for sweet potato breeding.